Multichannel advertising: does print advertising affect search engine advertising?. Issue 9 (19th August 2014) - Olbrich, Rainer; Schultz, Carsten D.
Abstract : Purpose: The study contributes to our understanding of search engine advertising in two main ways. Firstly, we analyze the comparative effectiveness of its campaign parameters. Secondly, we examine the multichannel effect of print advertising on search engine advertising. Design/methodology/approach: Based on advertising data for a three-year period, we test the hypotheses by means of a path model with the aid of partial least squares. Findings: The advertising budget and the degree of keyword matching yield the greatest effect on the number of signed contracts. The click-through rate and the bid amount contribute to a lesser extent to explaining this financial target variance. The number of keywords had no significant effect. The study did not yield significant evidence of print advertising directly affecting the number of search engine ad impressions, but showed an indirect effect of print advertising on the number of conversions, induced directly by search engine advertising. Research limitations/implications: The multichannel relationship of print and search engine advertising, including its campaign parameters, provides a starting point for future research to provide a coherent methodology for capturing the necessary data, processing the underlying information, and evaluating the advertising effects. Practical implications: The multichannel effect needs to be quantified and taken into account when evaluating print advertising and search advertising campaigns and the future advertising mix is planned. Originality/value: The study extends the field of search engine advertising in the direction of multichannel effects. In comparison to previous research, empirical evidence on the multichannel usage of print advertising and search engine advertising, related to an overall economic target, are provided.